4CPS-046 Glucocorticoids in chronic inflammatory diseases: assessment of patients' adherence. (2nd March 2018) - Jarraya, D; Jeddou, K Ben; Bouassida, M; Hasni, N; Lajnef, R; Kallel, I; Bourguiba, A; Ouahchi, Z; Ghlila, D
Abstract : Background: Glucocorticoids (GC) are widely used in the management of chronic inflammatory diseases. However, lack of patients' adherence leads to suboptimal effectiveness of GC therapy in real-life practice Purpose: The aim of this study is to identify factors which may lead to non adherence to oral GC in the treatment of chronic inflammatory diseases. Material and methods: Cross-sectional study included outpatients and inpatients in an internal medicine department. Patients who had been taking oral GC for more than 3 months prior to the study were enrolled. Adherence was measured using patient self-reports. Bivariate methods were used for analysis. Results: Ninety-seven patients (sex ratio=0.18), with a mean ±SD age of 51±13 years were enrolled. Patients interviewed were under GC therapy since an average of 7.71±5.75 years. The median daily GC dose was 16.35 mg (all patients were treated with prednisone). Fifty-three patients (55%) had poor adherence to GC. Major causes reported were occurrence of an adverse event, forgetfulness and a high number of pills respectively in 28, 24 and 13 patients. Female sex (p=0.032) and age greater than 40 years (p<0.000) were correlated to poor adherence. No relation had been demonstrated between adherence and maritial status (p=0. 215), regular activities (p=0.388), education level (p=0.181), length of treatment (p=0.95) and number of pills (p=0.439). In addition, this study revealed a problem with GC overuse in 20 patients. The reasons were symptom reduction, lack of information, distance follow-up appointments and easy access to GC from free-practice pharmacies. Conclusion: The results showed poor adherence in patients under GC. The occurrence of an adverse event was the main reason for non-adherence. Thus the setting-up of a therapeutic patient education programme would improve patient adherence and therefore quality and safety of GC therapy. No conflict of interest